An oxidative carbon-carbon bond-forming reaction proceeds via an isolable iminium ion - Tsang, Althea S.-K.; Jensen, Paul; Hook, James M.; Hashmi, A. Stephen K.; Todd, Matthew H. (Pure and applied chemistry, 2011)
The mechanism of our previously reported DDQ-mediated oxidative C-C bond-forming reaction is investigated. We are able to trap and characterize an iminium ion intermediate with X-ray crystallography, elemental analysis, and solid-state NMR spectroscopy; to our knowledge this is the first time this putative intermediate ion has been directly observed in such cross-dehydrogenative couplings (CDCs). The intermediate can be reacted with a range of nucleo-philes, including a malonate that is not amenable to a one-pot reaction protocol.